The Vicarious Trauma Scale: Confirmatory factor analysis and psychometric properties with a sample of victim advocates. (28th February 2018) - Benuto, Lorraine; Singer, Jonathan; Cummings, Caroline; Ahrendt, Andrew
Abstract: Vicarious trauma is referred to as the detrimental change in the manner that professionals understand and interpret material, as a result of exposure to second‐hand traumatic material (McCann & Pearlman [1990] Journal of Traumatic Stress, 3:131). According to Aparicio et al. ( Health & Social Work, 2013, 38:199), vicarious trauma comprises both affective and cognitive components and, while it is distinct from posttraumatic stress disorder (PTSD), it is associated with similar symptoms, including re‐experiencing and avoiding traumatic material and experiencing depressed mood. The purpose of this study was to analyse the psychometric properties of the Victim Trauma Scale (VTS) and provide additional support, supplementing the findings of Aparicio et al. (2013), but instead using victim advocates as participants ( n  = 142). The survey was open between February 2016 and February 2017. More than 96% of participants were in paid employment positions, as more than 80% reporting working 40 or more hours a week. Aparicio et al. (2013) found that the VTS was two‐dimensional (affective and cognitive); however, after examining the goodness of fit of the two‐factor model using a confirmatory factor analysis (CFA) approach, this study concluded that the two‐dimensional model was not a good fit. Due to the poor goodness of fit of the two‐factor model and the post hoc EFA resulting in a one‐factor model, our data do not support the findings of Aparicio et al. (2013). Further, the findings suggest the VTS is an acceptable measure of vicarious trauma, as demonstrated by the high internal consistency and the single‐factor loading.